COVID-19 Complicating Perioperative Management of Left Ventricular Assist Device Implantation - Belfort, D.S. (J Heart Lung Transplant, 2021)
INTRODUCTION: The coronavirus 2019 disease (COVID-19) affected almost 40 million people worldwide and caused more than one million deaths. Some conditions are associated with worse prognosis such as heart failure and left ventricular assist device (LVAD) recipients. CASE REPORT: A 31-year-old male patient without comorbidities was admitted due to cardiogenic shock and pneumonia. He required IABP and ECMO. The patient recovered from organ dysfunctions and ECMO was weaned off. He persisted dependent on dobutamine and IABP. Echocardiogram showed severe left ventricular dysfunction and moderate right ventricular dysfunction (RVD), but right heart catheterization revealed no pulmonary hypertension. SARS-CoV-2 RT-PCR was negative and myocardiopathy investigation was inconclusive after endomyocardial biopsy. LVAD implantation was planned as a bridge to transplant. A Heart Mate 3 was successfully implanted. The patient presented fever in the operating room and persisted febrile for 3 days. COVID-19 was suspected and SARS-CoV-2 RT-PCR was positive. He was extubated on 3(rd) postoperative day (POD) and echocardiogram showed only mild RVD. On 5(th) POD, he became hypoxemic requiring high flow nasal cannula, and chest X-ray revealed multiple pulmonary bilateral opacities. Antibiotics and corticosteroids were prescribed. Echocardiogram showed severe RVD and hemodynamic instability led to milrinone and dobutamine requirement in maximal doses. On 10(th) POD endotracheal intubation was required. The patient experienced severe acute respiratory distress syndrome (ARDS) and multiple complications: shock, bacterial pneumonia, hemothorax, pneumothorax due to barotrauma and bloodstream infection. He had no thromboembolic events. After 48 days he was free from mechanical ventilation and from inotropes. Echocardiogram showed moderate RVD and pulmonary artery systolic pressure 35mmHg. After 51 days he was discharged from the intensive care unit and is now in rehabilitation program. SUMMARY: Severe cases of COVID-19 are associated with a cytokine storm and a prothrombotic state. LVAD recipients are at particular risk of unfavorable outcomes. Besides the higher risk of thromboembolic events, LVAD recipients are more vulnerable to RVD in the setting of ARDS. This could be particularly critical during the perioperative management of RV failure as presented in this case.